The recent spike in illicit tobacco trade in South Africa - Ebrahim, Zeenat (School of Economics, 2020)
Since 2015, the South African National Treasury has experienced declines in tax-paid cigarette revenues. The declines have been attributed to upward spikes in the illicit tobacco trade. This dissertation explores the upward spike in the illicit tobacco trade, in order to assess whether or not a relationship exists between tobacco companies’ actions and the spike in illicit activity. The study analyses information gathered from semi-structured key informant interviews in order to derive expert insights into the spike. The results indicate that the tobacco industry as a whole is using a variety of tactics to protect their interests. This thesis suggests that the recent increase in the illicit tobacco trade is the result of an increase in under-declared cigarette production by the tobacco industry, which exploits a weak enforcement of antitobacco laws.